Physics, Smartphones and 3D-Print Technology: A Digital-Transition Case Study in Science Education - Larnder, Chris; Nebia, Faïza; Livingstone, Margaret; Huang, Shiwei (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education)

(untitled) (CRIFPE, 2020)
We describe the stages of technological development in a 4-year project designed to adapt college-level physics education to the realities of the digital era. The project is a case study that draws on a wide range of complementary innovations to provide a better overall understanding of how technological transitions take place in an educational setting and, in particular, in the education of students in science and engineering fields. The complete lifecycle of technological-change projects is examined. Various longer-term challenges are evaluated, including the development of new skills in teachers and support staff and the need for investments in equipment in participating educational institutions. Québec`s recent Digital Action Plan is used both as a reference funding framework for discussion and as an example of how individual technology-based projects can indirectly benefit from broader government investments that target the college network as a whole.